(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
It is a great pleasure to acknowledge that Trinity lnstitute of professional Studies is organizing the 11th TIPSCON- National Conference on the theme of "Resilience & Reinvention: A Path For Change ln Management, lT, Media and Law".The theme, set for this conference, is undeniably the promotion of not only academic and research but also to explore many research findings and achievements in various fields. I am certain that this occasion will be able to provide a platform towards strengthening relationship among researchers from diverse fields in knowledge sharing, while at the same time provide the necessary thrust in joint research collaborations I believe that the attendees will certainly benefit from this conference.I appreciate the organizing team for showing a keen interest in organizing successful conference to spread knowledge among members and authors. I wish the conference a grand success.